The use of Facebook in social work practice with children and families: exploring complexity in an emerging practice. Issue 2 (2nd April 2020) - Cooner, Tarsem Singh; Beddoe, Liz; Ferguson, Harry; Joy, Eileen
Abstract: This article draws from a 15-month participant observation study of social work and child protection practices in England to illustrate how social workers used Facebook to gain another view of service-users' lives. Social media use was not an intended focus for the study, its presence emerged during our data analysis. While some research has shown that such practices occur, our long-term ethnographic approach provides new insights into how Facebook was actually used in ongoing casework with families and why it was used. Our findings show that Facebook use took multiple forms. Some social workers actively searched service users' Facebook pages and some opposed any such usage. We further advance the literature by introducing a third group who were unwillingly "drawn into" acting on Facebook information presented to them by others such as their managers. Our research insights suggest that social work must pause to consider the implications of these complex emerging practices.